The War Correspondent - McLaughlin, Greg (London Pluto Press, 2002)
The War Correspondent looks at the role of the war reporter today in context with contemporary issues: the perks and the risks of the job; the tendency for western journalists to take sides in civil conflicts like Bosnia and Kosovo; the media politics of international intervention in humanitarian crises; the seductive power of military 'public relations'; and of course the commercial and technological pressures of an intensely concentrated, competitive news media environment. The book features interviews with prominent war and foreign correspondents such as John Pilger, Robert Fisk, Maggie O'Kane and Christiane Amanpour. A special case study in military-media relations during NATO's bombing of Serbia/Kosovo in 1999 suggests that in spite of widespread passivity among the correspondents who attended the daily briefings in Brussels, some sections of the news media were at least prepared to ask some hard questions of NATO strategy and policy. Greg McLaughlin argues that the future for war reporting and foreign correspondence will be determined not so much by professional imperatives but by military pressures and market forces outside the control of the journalist. The self-serving myth that war stories are no longer what 'consumers' want disguises the reality that foreign news is becoming too expensive to produce. Unless 'our boys' are directly involved in combat, wars and rumours of wars will continue to slip down the media agenda as 'the rest of the day's news'.
Includes Notes, Index. Bibliography and Appendices
Keywords: War--Press Coverage -- War Correspondents